Collaborative Risk Management in Food Bio-Packaging Supply Chains: A Qualitative Research - Barbara OCICKA; Jolanta TUREK (Communications of International Proceedings, 2023)
The purpose of the article is to identify the main drivers and types of bioplastic-related risk and to explore the multi-stakeholder collaboration potential for managing this risk in food bio-packaging supply chains. The use of bioplastics in the economy is becoming an important issue from a sustainable development perspective and the need for transformation towards closed-loop economies. Currently, packaging is one of the main users of virgin materials fossil-fuel based as 40% of plastics used in the EU is allocated for packaging (European Green Deal, 2019). There is a clear need to review the widespread use of plastics. It is already addressed by European regulations and the European Green Deal focusing on preventing packaging waste, stimulating reuse and refill, and making all packaging recyclable by 2030 (European Green Deal, 2019). In this context, there is significantly less knowledge available, and less attention paid in the literature to bioplastic-related risk identification and management than to plastic-related challenges. The authors’ considerations are based on the qualitative empirical research on food bio-packaging supply chains in the context of the circular economy principles. Two qualitative research methods were used: individual semi-structured in-depth interviews and focus group discussions organized according to the rules of Social Innovation Labs. The research findings contribute to the literature on food packaging supply chain management in the end-to-end and multi-stakeholder perspective. The conclusions may have practical implications for collaborative supply chain risk management by exploring potential of building bridges between stakeholders through their collaboration on social innovation development.
Keywords: bio-packaging; food supply chain; bioplastic-related risk; collaborative risk management; multi-stakeholder collaboration